2021
DOI: 10.31744/einstein_journal/2021ao6100
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypertension on arterial stiffness and cardiac autonomic modulation in patients with peripheral artery disease: a cross-sectional study

Abstract: Objective: To examine the impact of hypertension on cardiovascular health in patients with symptomatic peripheral artery disease and to identify factors associated with uncontrolled hypertension. Methods: A cross-sectional study including 251 patients with symptomatic peripheral artery disease (63.9% males, mean age 67±10 years). Following hypertension diagnosis, blood pressure was measured to determine control of hypertension. Arterial stiffness (carotid-femoral pulse wave velocity) and cardiac autonomic modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
2
0
2
Order By: Relevance
“…Compared to patients with normal PWV values, moderate, moderate–high, and high PWV values were responsible for a 3.03-, 5.44-, and 7.87-times higher incidence of hypertension, respectively [ 39 ]. Hypertension was associated with a higher carotid–femoral PWV, regardless of sex, age, ankle–brachial index (ABI), body mass index (BMI), walking capacity, and HR (ß = 2.59 ± 0.76 m/s, b = 0.318, p = 0.003) [ 40 ].…”
Section: Impact Of Metabolic Syndrome Components On Arterial Stiffnessmentioning
confidence: 99%
“…Compared to patients with normal PWV values, moderate, moderate–high, and high PWV values were responsible for a 3.03-, 5.44-, and 7.87-times higher incidence of hypertension, respectively [ 39 ]. Hypertension was associated with a higher carotid–femoral PWV, regardless of sex, age, ankle–brachial index (ABI), body mass index (BMI), walking capacity, and HR (ß = 2.59 ± 0.76 m/s, b = 0.318, p = 0.003) [ 40 ].…”
Section: Impact Of Metabolic Syndrome Components On Arterial Stiffnessmentioning
confidence: 99%
“…O controle da pressão arterial em pacientes com DAP é crucial, não apenas para reduzir o risco de complicações cardiovasculares, mas especificamente para minimizar o risco de AVC. Estratégias para gerenciar a hipertensão em pacientes com DAP devem incluir medicações anti-hipertensivas eficazes, ajustes dietéticos e aumento da atividade física, com monitoramento regular para garantir o cumprimento das metas de pressão arterial (Farah et al, 2021).…”
Section: Hipertensãounclassified
“…(16) Studies on amputations after revascularization for PAD have reported that amputation rates after lower limb revascularization procedures vary between 0 and 7%. (17,18) In the Brazilian health system, the registration of amputations does not allow identification of those that occur after revascularization attempts. Obtaining information on the time between revascularization and amputation, revascularization technique (open or endovascular), re-intervention rate, and amputation level (above or below the knee) is of fundamental importance to improve PAD care.…”
Section: Stroke After Carotid Revascularizationmentioning
confidence: 99%